Effect of Avocado Flesh (Persea Americana) Extract on HbA1c and Fasting Blood Glucose Levels in Type 2 Diabetes Mellitus Patients - Rahman, Shahrul; Septina, Lina; Nasution, Huwainan Nisa (Jurnal Kesehatan Masyarakat, 2024)
Diabetes mellitus is a complicated necessitates ongoing medical attention and is a serious health problem that has grown to worrisome proportions. The study aimed to assess the avocado pulp extract’s glycemic control in individuals with type 2 diabetes mellitus (T2DM) in a clinical setting in 2023. From the Klinik IMAN database, patients 18 years with T2DM who had previously been treated with oral hypoglycemic medications were included. The index date—the first day that avocado pulp extract was consumed—was used to collect baseline data. A laboratory measurements analysis was used to evaluate the change in glycated hemoglobin (HbA1c) and fasting blood glucose levels after a month of consuming avocado pulp extract and placebo. At one month, the percentage of patients who achieved their goal HbA1c and fasting blood glucose levels was determined. Overall, 30 patients were included and had baseline HbA1c and fasting blood glucose levels values available. Added avocado flesh extract not associated with improved HbA1c (0.04 [95% CI: -0.22-0.30], p0.05) and fasting blood glucose levels values (0.85 [95% CI: - 24.7-26.4], p0.05) versus baseline at a month. Added avocado flesh extract not associated with improved glycemic control during a month of follow-up in patients with T2DM.